The Blockchain Trilemma: A Formal Proof of the Inherent Trade-Offs Among Decentralization, Security, and Scalability - Souhail Mssassi; Anas Abou El Kalam (Applied Sciences)
Blockchain technology has emerged as a transformative force with the potential to disrupt traditional industries by providing decentralized, secure, and transparent systems. However, blockchain systems face a fundamental challenge known as the Blockchain Trilemma, which posits that a blockchain cannot simultaneously achieve optimal levels of decentralization, security, and scalability. This paper addresses the Blockchain Trilemma through rigorous mathematical proof, demonstrating that achieving maximum levels of all three properties concurrently leads to inherent contradictions. By formalizing the definitions of decentralization, security, and scalability, we provide a foundational framework to understand these trade-offs. Our analysis includes a proof by contradiction and computational complexity analysis. This work aims to deepen the understanding of the fundamental limitations of blockchain technology, offering insights for future innovations and helping navigate the inevitable trade-offs.